Marginalized Textile Producers in New Kingdom Egypt - Jordan Galczynski (Arts)
Textiles were ubiquitous in the elite Egyptian cultural sphere—from clothing, furniture coverings, and wall decorations to grave goods and temple offerings. The Egyptian world was draped in cloth, yet the producers were often marginalized members of society—immigrants, war captives, and women, who produced for a select few to whom they did not often belong. This paper aims to use textiles as a medium to investigate how the New Kingdom textile industry maintained social inequalities and power differentials. This paper highlights the efforts of marginalized labor in the production of textiles in New Kingdom Egypt, utilizing an intersectional approach to understand the interactions of the producers, varying levels of management, and elite consumers. Textiles were a high-value resource and one of the only goods that increased in value with labor, unlike other crafted goods, like metals, for example. I posit that this was inherently linked to the marginalization of the labor involved. The fabrics woven were a display of the Egyptian hegemony and reaffirmed the social order between the elites and the rest of society.